International business English class cassette sets 1-3 [soundrecording] - Jones, Leo; Alexander, Richard (Cambridge Cambridge University Press, 1989)
A group/class study on the fundamentals of English composition and communication skills in Business.
Keywords: English language -- Business English; Communication; Language